On resilience and acceptance in the transition to palliative care at the end of life. (May 2015) - MacArtney, John I; Broom, Alex; Kirby, Emma; Good, Phillip; Wootton, Julia; Yates, Patsy M; Adams, Jon
Specialist palliative care is a prominent and expanding site of health service delivery, providing highly specialised care to people at the end of life. Its focus on the delivery of specialised life-enhancing care stands in contrast to biomedicine's general tendency towards life-prolonging intervention. This philosophical departure from curative or life-prolonging care means that transitioning patients can be problematic, with recent work suggesting a wide range of potential emotional, communication and relational difficulties for patients, families and health professionals. Yet, we know little about terminally ill patients' lived experiences of this complex transition. Here, through interviews with 40 inpatients in the last few weeks of life, we explore their embodied and relational experiences of the transition to inpatient care, including their accounts of an ethic of resilience in pre-palliative care and an ethic of acceptance as they move towards specialist palliative care. Exploring the relationship between resilience and acceptance reveals the opportunities, as well as the limitations, embedded in the normative constructs that inflect individual experience of this transition. This highlights a contradictory dynamic whereby participants' experiences were characterised by talk of initiating change, while also acquiescing to the terminal progression of their illness.